Kajian Konflik Sosial Terhadap Kebijakan Social Safety Net Pada Era New Normal Di Kabupaten Cirebon - Ratna Puspitasari; Septiani Resmalasari (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2021)
In early 2020, corona disease 2019 (Covid-19) appeared in Wuhan, December 2019 and rapidly spread to almost around the world so that it is determined by WHO as pandemic since it has attacked 114 countries including Indonesia. The growth of Covid 19 was confirmed to have experienced a high spike as of September 4, 2020. There were 26 million people exposed to the Covid 19 virus, so the Indonesian government needs to provide social assistance for people affected by Covid-19. Based on the latest Worldometers update at the beginning of 2021, namely on Friday, January 8, 2021, the SAR CoV-2 corona virus has infected a total of 88.368.538 people worldwide with a calculation of 63.454.087 people who have recovered from infection while a total of 1.904.030 people were declared dead. The Covid-19 data and information center said a total of 494 people were suspected of being exposed to Covid-19. Minister of Social Affairs, Juliari Batubara ensured that 120.000 Beneficiary Families of the Family Hope Program (KPM PKH) in Cirebon Regency would receive a certain amount of rice as social assistance. There are 15 kilograms of rice in three distributions to help the food needs of the Beneficiary Families. The distribution of social assistance to communities affected by Covid-19 caused conflicts in several areas in Cirebon Regency which caused social turmoil as a result of social changes in the Covid-19 era. This study tried to examine the social conflicts that arise in the process of distributing social assistance in Cirebon with Karl Marx's theory of Social Conflict which consists of vertical conflict and horizontal conflict. This study used qualitative research methods and a phenomenological approach in the Covid-19 era as a tool for the researcher to analyze this study.